SOME WAYS TO FIND INTEGRALIZING MULTIPLICATORS - Usmanov Bakhtiyor Zoxirovich; Tagaynazarov Sirojiddin (Galaxy International Interdisciplinary Research Journal, 2022)
The article presents some special methods of the science of differential equations for solving complete differential equations and finding integral multipliers. The convenience and effectiveness of these methods are revealed.